PENGARUH PENGGUNAAN E-WALLET TERHADAP PERILAKU PRODUKTIF MAHASISWA STKIP PERSADA KHATULISTIWA SINTANG - Martina Cesilia J.A; Dessy Triana Relita; Yopinus Bobi; Avelius Dominggus Sore; Yulia Suriyanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The development of financial technology, particularly e-wallets, has changed the financial behavior of students in the digital era. This study aims to analyze the influence of e-wallet use on the productive behavior of students at STKIP Persada Khatulistiwa Sintang. This study used a quantitative approach with a correlational method. Data were collected through questionnaires from 100 respondents selected using a purposive sampling technique, then analyzed using simple linear regression. The results showed that e-wallet use had a positive and significant effect on students' productive behavior with a significance value of 0.000 < 0.05 and a coefficient of determination of 51.2%. These findings indicate that e-wallets function not only as a transaction tool but also as a means to improve efficiency, financial control, and student productivity. This study contributes to expanding fintech studies by emphasizing the role of e-wallets in shaping productive behavior among students. This research is limited by its sample size. It cannot represent respondents from a specific generation. Therefore, more in-depth research is needed to generalize the results.